Temporal Analysis of Hepatocyte Differentiation by Small Hepatocyte-Like Progenitor Cells during Liver Regeneration in Retrorsine-Exposed Rats - Gordon, Gavin J. (American Society for Investigative Pathology, 2000)
Liver regeneration after two-thirds surgical partial hepatectomy (PH) in rats treated with the pyrrolizidine alkaloid retrorsine is accomplished through the activation, expansion, and differentiation of a population of small hepatocyte-like progenitor cells (SHPCs). We have examined expression of the major liver-enriched transcription factors, cytochrome P450 (CYP) enzymes, and other markers of hepatocytic differentiation in SHPCs during the protracted period of liver regeneration after PH in retrorsine-exposed rats. Early-appearing SHPCs (at 3–7 days after PH) express mRNAs for all of the major liver-enriched transcription factors at varying levels compared to fully differentiated hepatocytes. In addition, SHPCs lack (or have significantly reduced) expression of mRNA for hepatocyte markers tyrosine aminotransferase and α-1 antitrypsin, but their expression levels of mRNA and/or protein for WT1 and α-fetoprotein (AFP) are increased. With the exception of AFP expression, SHPCs resembled fully differentiated hepatocytes by 14 days after PH. Expression of AFP was maintained by most SHPCs through 14 days after PH, gradually declined through 23 days after PH, and was essentially absent from SHPC progeny by 30 days after PH. Furthermore, early appearing SHPCs lack (or have reduced expression) of hepatic CYP proteins known to be induced in rat livers after retrorsine exposure. The resistance of SHPCs to the mitoinhibitory effects of retrorsine may be directly related to a lack of CYP enzymes required to metabolize retrorsine to its toxic derivatives. These results suggest that SHPCs represent a unique parenchymal (less differentiated) progenitor cell population of adult rodent liver that is phenotypically distinct from fully differentiated hepatocytes, biliary epithelial cells, and (ductular) oval cells.